Brush-controlled oriented growth of TCNQ microwire arrays for field-effect transistors. Issue 3 (21st December 2015) - Zhang, Peng; Tang, Qingxin; Tong, Yanhong; Zhao, Xiaoli; Wang, Guorui; Liu, Yichun
Abstract : We demonstrate a solution-based method by a writing brush to realize the controllable fabrication of highly-oriented and large-scale TCNQ microwire arrays, which can be grown on rigid and flexible substrates. Abstract : We demonstrate a novel solution-based assembly method using a writing brush to realize the controllable fabrication of highly-oriented and large-scale TCNQ single-crystal microwire arrays. The arrays can not only be grown on conventional rigid substrates, such as Si, Si/SiO2 and low-cost glass, but also on nonconventional substrates, which include flexible polyethylene terephthalate (PET), curved glass hemispheres and commercially available plastic contact lenses. Their morphology is optimized by tuning solution concentration, substrate temperature, brush type, inclination angles and pressure of the brush. The length of the microwire arrays can extend to the millimeter level, and their preferential orientation is perpendicular to the lengthwise direction of the brush hair. The coverage area of microwire arrays with a consistent orientation can reach 1.5 × 2.0 mm 2 and the success ratio is as high as 93%. Based on these microwire arrays, devices on different substrates, including rigid Si/SiO2 and flexible PET, can be easily realized in one step. The anisotropic transport of TCNQ crystals is studied with respect to the concentration controlled morphology. All these results illustrate the broad application prospects of this facile writing-brush method in the growth of large-scale, high-quality organic micro/nanowires for integration into flexible organic semiconductor devices and circuits.